Identifikasi Alat Permainan Edukatif Dalam Mengembangkan Sains Sederhana Pada Anak Usia Dini Di Kecamatan Brang Rea Kabupaten Sumbawa Barat - Tiara Hesti Amanda; Gunawan Gunawan; Baik Nilawati Astini (Indonesian Publication Center, 2023)
Early childhood education (PAUD) is one of the educational institutions in Indonesia which has an important role to play in preparing superior generations as early as possible. students needed. This study aims to provide a more in-depth description of the identification analysis of educational game tools (APE) in developing simple science in early childhood. The results of this research ultimately obtained data that described the analysis of APE identification in developing early science in early childhood in Brang Rea District, West Sumbawa Regency, NTB. Based on the data obtained, it shows that there are as many as 6 types of APE that exist and are used to stimulate simple science in early childhood; there are 3 types of APE that are most dominantly used in stimulating simple science for early childhood; and as many as 4 types of APE which are dominantly suitable for use to stimulate early science in early childhood in Brang Rea District, West Sumbawa Regency.